LITERASI PENDIDIKAN DASAR (SEKOLAH DASAR) DAN PERMASALAHANNYA - Ananda, Rizki; Syafputri; Rudini Aprilia, Putri; Maiyolanda, Agnita; Rahmadani, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Literacy at the basic education level is a fundamental aspect in shaping students' academic skills and character. This study aims to comprehensively examine various concepts, implementation and problems of literacy at the primary school level through a qualitative approach with a literature review method. Data sources were obtained from relevant national and international journals published in the last five to ten years. The results show that literacy is not only related to technical reading and writing skills, but also the foundation of students' critical and reflective thinking. Although the government has rolled out various policies such as the School Literacy Movement (GLS) and the Merdeka Curriculum, their implementation has faced various obstacles such as limited facilities, low teacher competence and lack of parental involvement. Therefore, cross-sectoral synergy is needed to build a literacy ecosystem that is holistic, sustainable and contextual to the needs of children at primary school age.